“Health inequalities in Armenia - analysis of survey results” - Tonoyan Tamara; Muradyan Lusine (International Journal for Equity in Health, 2012)
Abstract Introduction Prevailing sociopolitical and economic obstacles have been implicated in the inadequate utilization and delivery of the Armenian health care system. Methods A random survey of 1,000 local residents, from all administrative regions of Armenia, concerned with health care services cost and satisfaction was conducted. Participation in the survey was voluntary and the information was collected using anonymous telephone interviews. Results The utilization of health care services was low, particularly in rural areas. This under-utilization of services correlated with low income of the population surveyed. The state funded health care services are inadequate to ensure availability of free-of-charge services even to economically disadvantaged groups. Continued reliance on direct out-of pocket and illicit payments, for medical services, are serious issues which plague healthcare, pharmaceutical and medical technology sectors of Armenia. Conclusions Restructuring of the health care system to implement a cost-effective approach to the prevention and treatment of diseases, especially disproportionately affect the poor, should be undertaken. Public payments, increasing the amount of subsidies for poor and lower income groups through a compulsory health insurance system should be evaluated and included as appropriate in this health system redesign. Current medical services reimbursement practices undermine the principle of equity in financing and access. Measures designed to improve healthcare access and affordability for poor and disadvantaged households should be enacted.